The frequency of wearing protective eyewear and face shield at educational hospital and public service Hospital in Makassar - Rasmidar Samad; Ummul Rawiyah; Cisilia Septiany (DiscoverSys Inc., 2017)
Objective: The aim of this study is to explore the comparison of frequency of wearing a protective eyewear and face shield at educational hospital and public service hospital in Makassar.Material and Method: This study is a descriptive research. It was conducted in March 2017 at dental hospital Hasanuddin University and at the dental and oral health service center (PPKGM) in Makassar. The subjects of the study are clinical students, dental professionals (resident), and dentist at department of periodontics and conservative at dental hospital Hasanuddin University and PPKGM. This research was done under direct observation on the subject of research. A descriptive analysis was done.Results: Number of operators at dental hospital Hasanuddin University who wore a protective eyewear were as many as 6 operators (5%) and none of the operators wore face shields while working. While in PPKGM the number of operators who wore a protective eyewear were as much as 4 operators (19%) and 11 operators (52%) wore face shields while working.Conclusion: The frequency of wearing protective eyewear and face shields at dental hospital Hasanuddin University is minimal and much lower than in PPKGM.